IMPLICATIONS OF CONSTITUTIONAL COURT DECISION NUMBER 003/PUU-IV/2006 ON THE APPLICATION OF UNLAWFUL ELEMENTS IN ARTICLE 2 OF THE CORRUPTION ERADICATION LAW - Febri Fitra Kusuma; I Nyoman Nurjaya; Yuliati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
One of the elements found in Article 2 of the Corruption Law is the element of illegality. In the explanation of Article 2, it is stated that "illegality" refers to both material and formal illegality. However, in 2006, the Constitutional Court issued a decision regarding the Formal Review of the phrase "illegality" in Article 2 of the Corruption Law through Constitutional Court Decision Number 003/PUU-IV/2006. In this decision, the judges declared that the explanation in Article 2 of the Corruption Law no longer has legally binding force. This means that the element of illegality in Article 2 of the Corruption Law can only be interpreted as a formal illegality element. Nevertheless, in practice, there are still court decisions that interpret the element of illegality in Article 2 of the Corruption Law as a material illegality element. Using the normative juridical research method, this study aims to address the issues related to the implementation of the element of illegality in Article 2 of the Corruption Law after the issuance of Constitutional Court Decision Number 003/PUU-IV/2006. This study concludes that judges can still interpret the element of illegality in Article 2 of the Corruption Law as a material illegality element by considering Article 28 paragraph (1) of Law No. 4 of 2004 concerning the Judicial Authority, which states "Judges are obliged to explore, follow, and understand the legal values and sense of justice prevailing in society."